Indigenous Life Projects and Extractivism Ethnographies from South America - Vindal Ødegaard, Cecilie; Rivera Andía, Juan Javier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Exploring indigenous life projects in encounters with extractivism, the present open access volume discusses how current turbulences actualise questions of indigeneity, difference and ontological dynamics in the Andes and Amazonia. While studies of extractivism in South America often focus on wider national and international politics, this contribution instead provides ethnographic explorations of indigenous politics, perspectives and worlds, revealing loss and suffering as well as creative strategies to mediate the extralocal. Seeking to avoid conceptual imperialism or the imposition of exogenous categories, the chapters are grounded in the respective authors' long-standing field research. The authors examine the reactions (from resistance to accommodation), consequences (from anticipation to rubble) and materials (from fossil fuel to water) diversely related to extractivism in rural and urban settings. How can Amerindian strategies to preserve localised communities in extractivistcontexts contribute to ways of thinking otherwise?
1. Introduction -- 2. Controlling Abandoned Oil Installations: Ruination and Ownership in Northern Peruvian Amazon -- 3. Extractive Pluralities: The Making of Life-worlds where Oil Wealth and Informal Gold Mining Intersect in Venezuelan Amazonia -- 4. In the Spirit of Oil: Unintended Flows and Leaky Lives in Northeastern Ecuador -- 5. Translating Wealth in a Globalised Extractivist Economy: Contrabandistas and Accumulation by Diversion -- 6. Water as Value and Being: Extractivist MegaProjects and Ownership in Peru -- 7. Indigenous Land Ownership in an Extractivist Context: Conflicting Compositions of the Environment in Cañaris (Peruvian Andes) -- 8. Carbon and Biodiversity Conservation as Resource Extraction: Enacting REDD+ Across Cultures of Ownership in Amazonia -- 9. Symbols of Resistance: Translating Nature, Indigeneity, and Place in Mining Activism -- 10. Performing Indigeneity in Bolivia: The Struggle over the TIPNIS.
Keywords: Ethnology; Social structure; Equality; Ethnology -- Latin America; Culture; Energy policy; Energy and state; Environmental policy; Ontology; Ethnography; Social Structure; Latin American Culture; Energy Policy, Economics and Management; Environmental Policy; Ontology